Deciphering the association between the Life’s Essential 8 and infertility: insights into depression, inflammation, and metabolic mediation - Cui, Shichao; Li, Li; Qin, Weibing; Liu, Wensheng; Zhong, Xingming (Frontiers in Endocrinology, 2025)
BackgroundThe Life’s Essential 8 (LE8) score has been associated with various health outcomes, but its relationship with female infertility remains unclear.MethodsThis study investigated the relationship between LE8 and infertility in women aged 20-45 years using the National Health and Nutrition Examination Survey (NHANES) data from 2013 to 2020. Weighted multifactorial logistic regression models were utilized to examine the association between the LE8 factors and their two subgroups [health behavior score (HBS) and health factor score (HFS)], as well as depressive status and infertility. Nonlinear relationships were examined using weighted restricted cubic spline (RCS) regression. Subgroup analysis and mediation analysis of depression, metabolic, and inflammation further elucidated the relationships. Sensitivity analysis was conducted to ensure the robustness of the findings.ResultsA total of 2,182 participants were included in this study, with 304 in the infertility cohort. Multifactorial regression analysis revealed significant negative correlations between LE8 and its subgroup HFS with infertility. Among the eight subscales, scores for sleep health, body mass index, and blood glucose were significantly negatively correlated with depression, while Patient Health Questionnaire-9 (PHQ-9) scores showed a positive correlation with infertility. Weighted RCS regression modeling indicated no nonlinear relationships between LE8, depression, HFS, HBS, and infertility. Mediation analyses suggested that depression scores, systemic immune inflammation index (SII), and uric acid (UA) mediated the association between LE8 and infertility.ConclusionHigher LE8 scores, indicating better cardiovascular health, are associated with lower depression scores and reduced levels of SII and UA. These factors collectively contribute to a lower risk of infertility in women. Targeted interventions aimed at enhancing cardiovascular health may potentially mitigate infertility risk through these pathways.